THE AWARENESS OF AUDIOVISUAL AND CULTURAL REALITY OF FUTURE ELEMENTARY EDUCATION TEACHERS - Warzocha, Anna Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Current cultural paradigm, founded on audiovisuality, creates new hierarchy, sets its own rules, brings dislocation on the stage of social communication, institutes new semiotic code, redefines the anthropological interpretation of a human being, at the same time generating different possibilities and different needs of a child at the elementary level of education. If one is to accept the assertion, that the organized process of education should be incorporated in cultural and civilizational context, and if one took into consideration the scientific research, claiming that as a result of new media expansion school pupils and students get to know the world mostly outside their schools, then cultivating teachersʼ awareness in the field of audiovisual culture consequences, especially within the system of elementary education, becomes the urgent need. Meanwhile, university courses, dealing with youngest pupils educational activities, very rarely offer lectures on anthropology, culture or media science, thus the knowledge which is absolutely necessary to run a reflective practice. Present article is by extension the comparison of research, which aimed at becoming acquainted with the amount of information on the subject of audiovisual culture and its implications, acquired by university students of elementary education  courses. The method of diagnostic survey was applied in the research carried out in the year 2018, and the results demonstrate clearly the respondentsʼ weak uptake of modern world regularities, which, by overpraising audiovisuality, brings changes in every area of our life.